2009
DOI: 10.1007/s00421-009-1307-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heavy strength training on thigh muscle cross-sectional area, performance determinants, and performance in well-trained cyclists

Abstract: This file was dowloaded from the institutional repository Brage NIH -brage.bibsys.no/nih Rønnestad, B. R., Hansen, E. A., Raastad T. (2010). Effect of heavy strength training on thigh muscle cross-sectional area performance determinants and performance in well-trained cyclists. ] and mean power output in the 40-min all-out trial were improved in E+S (p<0.05). For E, only performance in the 40-min all-out trial tended to improve (p=0.057).The two groups showed similar increases in VO 2max (p<0.05). In conclusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

25
161
7
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 115 publications
(194 citation statements)
references
References 53 publications
(76 reference statements)
25
161
7
1
Order By: Relevance
“…The W max as well as the mean and peak power output in a Wingate test reflect the ability to generate high power output over a short period of time. Peak power output in the Wingate test has been reported to be increased after a period of strength training in both non-cyclists (Beck et al 2007) and cyclists (Bastiaans et al 2001;Rønnestad et al 2010). These findings are supposedly explained by the facts that peak power output in cycling is affected by leg muscle cross-sectional area (CSA) and that strength training increases this CSA (Izquierdo et al 2004).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The W max as well as the mean and peak power output in a Wingate test reflect the ability to generate high power output over a short period of time. Peak power output in the Wingate test has been reported to be increased after a period of strength training in both non-cyclists (Beck et al 2007) and cyclists (Bastiaans et al 2001;Rønnestad et al 2010). These findings are supposedly explained by the facts that peak power output in cycling is affected by leg muscle cross-sectional area (CSA) and that strength training increases this CSA (Izquierdo et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…However, the effect of strength training on endurance cycling performance and traditional indicators of cycling performance like lactate threshold, maximum aerobic power output (W max ), and cycling economy, is still somewhat unclear. Importantly, adding strength training to usual endurance training does not appear to negatively affect maximal oxygen consumption (VO 2max ) in cyclists (Bishop et al 1999;Hausswirth et al 2010;Rønnestad et al 2010). Strength training has been shown to improve lactate threshold in untrained individuals (Marcinik et al 1991).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it has been reported that concurrent heavy strength training and endurance training in well-trained cyclists result in enhanced cycling performance. [1][2][3][4] Other research groups have previously failed to find a similar positive effect of strength training on performance in trained cyclists. 5,6 In one of our previous articles, cycling performance was determined as the power output in a 5-minute all-out trial performed subsequent to 185 minutes of submaximal cycling.…”
mentioning
confidence: 99%